Love and roast chicken : a trickster tale from the Andes Mountains - Knutson, Barbara (Minneapolis : Carolrhoda Books, 2004)
In this folktale from the Andes, a clever guinea pig repeatedly outsmarts the fox that wants to eat him for dinner.
Notable/Best Books (A.L.A.).
School Library Journal starred.
Wilson's Children.
4.2
K-3
Keywords: Guinea pigs -- Andes Region -- Folklore; Indians of South America -- Andes Region -- Folklore; Tricksters -- Andes Region; Folklore -- South America; Guinea pigs -- Folklore; Indians of South America -- Andes Region -- Folklore; Tricksters -- Folklore; Folklore -- South America; Guinea pigs -- Folklore; Native Americans -- Folklore -- Andes Region; Tricksters -- Folklore